The Tetrahymena chaperonin subunit CCT eta gene is coexpressed with CCT gamma gene during cilia biogenesis and cell sexual reproduction - Cyrne, Luísa (1996)
We report here the cloning and the characterization of the T. pyriformis CCT eta gene (TpCCT eta) and also a partial sequence of the corresponding T. thermophila gene (TtCCT eta). The TpCCt eta gene encodes a protein sharing a 60.3% identity with the mouse CCT eta. We have studied the expression of these genes in Tetrahymena exponentially growing cells, cells regenerating their cilia for different periods and during different stages of the cell sexual reproduction. These genes have similar patterns of expression to those of the previously identified TpCCt gamma gene. Indeed, the Tetrahymena CCT eta and CCT gamma genes are up-regulated at 60-120 min of cilia recovery, and in conjugation when vegetative growth was resumed and cell division took place. Our results seem to indicate that both CCT subunits play an important role in the biogenesis of the newly synthesized cilia of Tetrahymena and during its cell division.